Lateral entorhinal cortex afferents reconfigure the activity in piriform cortex circuits - Pedroncini, Olivia (2024)
Odours are key signals for guiding spatial behaviours such as foraging and navigation in rodents. It has recently been found that odour representations in the piriform cortex (PCx) can also contain information about their spatial context. However, the precise origins of this information within the brain and its subsequent integration into the microcircuitry of the PCx remains unknown. In this study, we focus on the lateral entorhinal cortex (LEC) as a candidate for carrying spatial contextual information to the PCx, to investigate how it affects the PCx microcircuit and its response to olfactory inputs. Utilising mice brain slices, we performed patch clamp recordings targeting both superficial (SP) and deep (DP) pyramidal neurons, as well as parvalbumin (PV) and somatostatin (SOM) inhibitory interneurons. Concurrently, we optogenetically stimulated excitatory LEC projections to study their impact on PCx activity. We found that LEC inputs are heterogeneously distributed in the PCx microcircuit, evoking larger excitatory currents in SP and PV neurons compared to DP and SOM neurons, respectively, due to their higher monosynaptic connectivity. Moreover, LEC inputs exert a differential effect on the inhibitory circuits, activating PV while suppressing SOM interneurons. We further studied the interaction among LEC inputs and the sensory afferent signals originating from the lateral olfactory tract (LOT) onto the PCx. Our findings demonstrated that both SP and DP neurons show a general increase in their spiking response when LEC and LOT are simultaneously activated. Notably, DP neurons exhibit a sharpening of their response attributable to LEC-induced inhibition that effectively suppresses the delayed spikes evoked by LOT stimulation. These observations suggest a regulatory mechanism whereby LEC inputs inhibit recurrent activity by activating PV interneurons. Our results show that LEC afferents reconfigure PCx activity and contribute to the understanding of how odour objects are formed within the PCx integrating both olfactory and contextual information.